Aspirin, metformin, and statin use on the risk of gastric cancer: A nationwide population‐based cohort study in Korea with systematic review and meta‐analysis - Seung In Seo; Chan Hyuk Park; Tae Jun Kim; Chang Seok Bang; Jae Young Kim; Kyung Joo Lee; Jinseob Kim; Hyon Hee Kim; Seng Chan You; Woon Geon Shin (Cancer Medicine, 2022)
Abstract Background/Aims Although several chemopreventive drugs against gastric cancer have been proposed, their effects have not been fully evaluated. We examined the impacts of aspirin, metformin, and statin use on gastric cancer development in a population‐based cohort in Korea. Methods We analyzed the association between potential chemopreventive drugs—aspirin, metformin, and statin—and gastric cancer through the Observational Medical Outcomes Partnership Common Data Model‐based Korean nationwide cohort. Use of aspirin, metformin, and statin was defined by ≥365 days of prescriptions for each drug in the general population. To summarize the current evidence, we further performed a systematic review and meta‐analysis of the impact of aspirin, metformin, and statin on gastric cancer development. Results After propensity score matching, 31,839, 6764, and 10,251 subjects were observed for medians of 4.7, 4.2, and 4.2 years for aspirin, metformin, and statin analysis, respectively. Use of aspirin or statin was associated with lower risks of gastric cancer compared to their non‐use, respectively (hazard ratio [HR] [95% confidence interval [CI]]: aspirin, 0.72 [0.60–0.85], p < 0.01; statin, 0.67 [0.49–0.92], p = 0.01). However, no association was observed between metformin use and gastric cancer development (HR [95% CI]: 0.85 [0.59–1.23], p = 0.40). A subgroup of subjects with diabetes mellitus showed a lower risk of gastric cancer development with statin use. The meta‐analysis showed the highest effect size of gastric cancer development for statin, followed by aspirin and metformin. Conclusions Statin and aspirin use were associated with significantly reduced risks of gastric cancer development, while the use of metformin was not associated with the gastric cancer risk. The protective effect of statin against gastric cancer was also significant in patients with diabetes mellitus.